IDENTIFIKASI ASPEK SIMBOL DAN NORMA KULTURAL PADA ARSITEKTUR RUMAH TRADISIONAL DI MINAHASA - Octavianus Hendrik Alexander Rogi & Wahy (EKOTON, 2013)
This research's objective is to identify the symbolic aspects and cultural values that lie beneath the phisical performance of the traditional architecture of Minahasa, especially the architecture of the traditional houses. This research is purely descriptive, and basically relies on textual references study, field observations towards few traditional houses treated as samples of study, and contextual interviews with some reliable informants.As a result, this study shows that the architecture of Minahasa traditional houses is an evolutive form. It evolved from the earlier form that was created pragmatically, in the context of providing shelter for men as a respond to the harsh dan uncomfort physical environment. In the long span of time, the evolution was determined mainly by the cultural contact in the era of Dutch Collonialism in Minahasa, and the variation of cultural schemes develop by each sub tribes of Minahasa